Conflicts-law constitutionalism in the EMU: how much unity can European diversity sustain? - Anna Peychev (European Law Open)
The core of the contract between economic and monetary union is set in not so much the formally legal, if economically irrational and practically contentious, divide of the Treaties, but rather, the rules for governing the right balance of EMU are found in its economic governance framework, set up to condition national budgetary policies into optimal function in service of Union monetary policy. Within those rules we can differentiate two ‘worldviews’ of constitutionalism. The first we may refer to as ‘optimal function EMU’ where sovereigns are equal, democracies may pick their own socio-economic policy and make equally valid claims to be managed by the conflicts law approach of cooperation within the preventive arm of the European Semester based on Article 121 TFEU, and where we may pretend the economic-monetary divide erected by law is a real, tangible phenomenon. The alternative version of constitutionalism is found beyond ‘optimal function EMU’, in fact, as soon as any risk to the model arises. This worldview institutes a strict legal hierarchy that establishes monetary supremacy over the economic realm. Within this setup, the very existence and proper function of the single currency rationalise the ultimate truth – that all Member States are equal, but some are more equal than others. Can conflicts law constitutionalism offer a way to recalibrate unity and diversity in a format fit for the purposes of the contemporary financial and economic context, while simultaneously re-claiming the space for national collective choice and protecting Union values?